Protocol for a multicentre, prospective observational cohort study in Japan: association among hospital-acquired disability, regular exercise and long-term care dependency in older patients after cardiac surgery - Tetsuya Takahashi; Kentaro Iwata; Hidetaka Watanabe; Masayuki Tahara; Masakazu Saitoh; Tomoyuki Morisawa; Akihiro Sakuyama; Koji Sakurada; Yusuke Hanafusa; Yusuke Ochi; Go Takamura; Akira Minei (BMJ Open)
Introduction Cardiac surgery for older patients, postoperative functional decline and the need for long-term care have received increasing attention as essential outcomes in recent years. Therefore, prevention of functional decline and long-term care dependency after cardiac surgery are important; however, our current understanding of postoperative functional trajectory and effects of postoperative regular exercise on long-term functional decline and long-term care dependency is limited. Therefore, we will conduct a multicentre, prospective cohort study to (1) examine the effect of hospital-acquired disability on long-term functional decline and long-term care dependency and (2) investigate the favourable effect of postoperative regular exercise on long-term functional decline and long-term care dependency in older patients after cardiac surgery.Methods and analysis We designed a prospective, multicentre cohort study to enrol older patients aged≥65 years undergoing elective coronary artery bypass graft or valve surgery. We will conduct medical record reviews to collect data on patient demographics, comorbidities, operative details, progression of in-hospital postoperative cardiac rehabilitation and functional trajectory from a few days before cardiac surgery to the day before hospital discharge. They will be followed up for 2 years to obtain information on their health status including functional status, regular exercise and clinical events by mail. Primary endpoints of this study are long-term functional decline and long-term care dependency after cardiac surgery. Secondary endpoints are readmission due to cardiac events or all-cause mortality.Ethics and dissemination The study protocol was approved by the Ethics Committee of the Department of Physical Therapy, Faculty of Health Science, Juntendo University, and of each collaborating hospital. We obtained written informed consent from all study participants after the description of the study procedures. Publication of the study results is anticipated in 2025.